Evaluation of Floods Susceptibility Models Based on Different Pairwise Parameters in the Analytical Hierarchy Process: Case Study Cilemer and Ciliman Watersheds - Dian Noor Handiani; Ditto Purnomo (Journal of Natural Resources and Environmental Management, 2024)
This study investigated flood vulnerability in the Ciliman and Cilemer Watersheds, situated in Banten Province, and employs a spatial multi-criteria-integrated approach, with a specific focus on the Analytical Hierarchy Process (AHP). Two distinct scenarios, which have different parameter priority, were compared: one based on expert judgment for pairwise parameter comparisons (scenario-1) and the other derived from historical flood occurrences in high and very high vulnerability areas (scenario-2). Seven parameters, including elevation, slope, precipitation, geologic, soil type, land use, and distance to streams were weighted substantially different between the two scenarios. The study validated the flood vulnerability scenarios by contrasting them with historical flood data. Scenario-2 exhibited a closer agreement with the historical flood points during validation, particularly in very high vulnerability areas. Elevation and slope are identified as pivotal factors influencing flood vulnerability: low elevations and gentle slopes increased vulnerability, while higher slopes decreased flood susceptibility.